Increasing productivity of meatball SMEs through the application of appropriate technology for meatball forming machines - I Made Arsana; I Wayan Susila; Mochamad Cholik; Novi Sukma Drastiawati (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Meatballs are generally made from meat that is ground and built with flour. The results of this process are called pentol. Mr Jiman's meatball business which is located in Nganjuk Regency, still used conventional methods. This can affect the amount of pentol production because it still involves human labour. The method used also affects the shape and size, which is the unequal shape and needs a tool that improves this performance. Most of the equipment currently available in the market is a product with a large capacity, unreachable prices, expensive maintenance, and difficulty in obtaining spare parts. To solve partner problems, develop equipment in the form of a meatball forming machine with an electric motor. The method of making a machine is carried out in several stages: designing, measuring and cutting materials, manufacturing, assembling, and testing processes. This purpose is to increase meatball productivity. The results were obtained by using a meatball forming machine with a speed of 4 meatballs/second so that it has increased the efficiency of production time by 400% compared to the manual method, which produces one meatball/second. The productivity of business profits increased 43.7% compared to the previous one, which still used conventional processes.